2004
DOI: 10.1161/01.cir.0000134959.83967.2d
|View full text |Cite
|
Sign up to set email alerts
|

TIMP-3 Deficiency Leads to Dilated Cardiomyopathy

Abstract: Background-Despite the mounting clinical burden of heart failure, the biomolecules that control myocardial tissue remodeling are poorly understood. TIMP-3 is an endogenous inhibitor of matrix metalloproteinases (MMPs) that has been found to be deficient in failing human myocardium. We hypothesized that TIMP-3 expression prevents maladaptive tissue remodeling in the heart, and accordingly, its deficiency in mice would alone be sufficient to trigger progressive cardiac remodeling and dysfunction similar to human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
113
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(120 citation statements)
references
References 33 publications
6
113
1
Order By: Relevance
“…Our results seem to conflict with previous data showing that TIMP-3 KO, obtained by embryonic knockdown of the gene, led to natural deterioration of cardiac structure and function with aging 30 and accelerated transition to heart failure on TAC. 16 These effects were ascribed mainly to a dysregulated TACE activation and excessive cytokine production, leading to exacerbated inflammation, fibrosis, and hypertrophy and recognizing that maladaptive matrix remodeling promotes abnormal cardiac structure and function.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results seem to conflict with previous data showing that TIMP-3 KO, obtained by embryonic knockdown of the gene, led to natural deterioration of cardiac structure and function with aging 30 and accelerated transition to heart failure on TAC. 16 These effects were ascribed mainly to a dysregulated TACE activation and excessive cytokine production, leading to exacerbated inflammation, fibrosis, and hypertrophy and recognizing that maladaptive matrix remodeling promotes abnormal cardiac structure and function.…”
Section: Discussioncontrasting
confidence: 99%
“…Inflammation plays an important role in the progression to cardiac hypertrophy (20), and perivascular infiltration by neutrophils and macrophages has been observed in the hearts of several animal species subjected to AB (30,31). After curcumin administration, we observed marked attenuation of leukocyte infiltration and cytokine production, suggesting potential cross-talk between leukocyte infiltration and inflammation in modulating the microenvironment for the development of cardiac hypertrophy.…”
Section: Figurementioning
confidence: 62%
“…Additionally, the present study demonstrates that fetal hypoxia increases TIMP-3 and TIMP-4 expression levels in both fetal and neonatal hearts, suggesting another possible mechanism in the hypoxia-mediated downregulation of myocyte proliferation. In addition to the roles in modulating MMPs, it has been demonstrated that both TIMP-3 and TIMP-4 play a key role in inhibiting cardiomyocyte proliferation in rat hearts possibly in a MMP-independent and receptor-mediated manner (13,16,17,42).…”
Section: Discussionmentioning
confidence: 99%